Atypical Aeromonas salmonicida -infection as a threat to farming of Arctic charr (Salvelinus alpinus L.) and European grayling (Thymallus thymallus L.) and putative means to prevent the infection - Pylkkö, Päivi (University of Jyväskylä, 2004)
Päivi Pylkön väitöskirjatutkimus osoittaa harjuksen ja nieriän olevan lohikaloista herkimpiä epätyyppisen Aeromonas salmonicida (aAS)–bakteerin aiheuttamalle tulehdukselle. Tautia esiintyy vuosittain useimmilla harjusta ja nieriää viljelevillä laitoksilla. Laitoskasvatus on ensiarvoista vaarantuneiden harjus- ja erittäin uhanalaisten nieriäkantojen säilymiselle. This review summarizes the results of studies on atypical Aeromonas salmonicida (aAS) -infection among farmed Arctic charr (Salvelinus alpinus) and European grayling (Thymallus thymallus) (later referred as charr and grayling, respectively). Specifically, I aimed to characterize the causative agent of aAS -infection, to describe putative virulence factors of the bacteria and cross pathology of the infection in charr and grayling. I also aimed to describe some of the immune defense functions in charr. I also described a concomitant presence of a common fresh water fish parasite, Diplostomum spathaceum, and aAS -bacteria in manifestation of the bacterial infection. The experimental juvenile charr and grayling, originated from Vuoksi, Kymijoki and Inari watercourses in Finland. Several (n=66) aAS isolates from 7 watercourses in Finland and from the Baltic sea were characterized in the study. These were compared to 11 Swedish, 1 Icelandic aAS isolates, to 3 A. salmonicida subsp. salmonicida (ASS) isolates and to ATCC 33659, a type strain for A. salmonicida subsp. achromogenes. Classical biochemical analyzes and modern molecular tools (macrorestricted genome and plasmid profiles) were utilized in characterizing. AAS was detected from fish tissue (intestine, lens and heart) by a combination of bacterial cultivation and polymerase chain reaction (PCR) techniques. Pathology of aAS infection in charr and grayling was described both in natural outbreaks at fish farms and after experimental challenge. The effects of oil-adjuvanted vaccine on the immune system and on the growth of charr at different post vaccination (p.v.) temperatures was studied. Interactions ...